Indigenous healers and stuttering - Rozanne Platzky; Joan Girson (South African Journal of Communication Disorders, 1993)
Traditional beliefs and attitudes of Black South Africans to stuttering were investigated. Four Indigenous Healers (IHs) from different ethnic groups were interviewed about their beliefs as to cause and management of stuttering, as well as the outcome of their treatment. The data reveals varying degrees of concern about stuttering. The traditional beliefs of cause and management of stuttering show some similarities to current beliefs held by speech pathologists. Implications in terms of the direction in therapy, cooperation with IHs and future research in this field are discussed.